Superior hue output as well as lumen for WLEDs with dual-sheet distant layouts of phosphor - Phuc Dang Huu; Phan Xuan Le (Universitas Ahmad Dahlan, 2022)
Remote phosphor constructions usually have color quality drawbacks but are more luminous in terms of lumen, surpassing conformal phosphor or in-cup layouts of phosphor. From this disadvantage, there is a great number of studies carried out to boost the chromatic performance in remote phosphor (RP) structures. This work focuses on using a two-layer RP or dual-film RP (DFRP) to improve the color rendering indices (CRI) as well as color quality scales (CQS) for white light emitting diodes (WLEDs). Two equivalent dual remote phosphor (DRP) structures for WLEDs operating at various temperatures of color including 5600 K, 7000 K, as well as 8500 K will be employed for our study. The study’s idea involves putting one phosphor Zn2SiO4:Mn2+,P layer or one red phosphor Mg2SiO4:Mn2+ layer on top of the yellow YAG:Ce3+. Subsequently modifying the concentration for each red and green phosphor to investigate the changes in color metrics and luminous flux. As a result, a suitable red and green phosphor concentration can be determined to acquire desired outcomes for each DFRP-WLED. Obtained results show that Mg2SiO4:Mn2+ performs significant boosting on both CRI and CQS, especially when being integrated with increasing concentration, thanks to the increased red-light presence for the WLED device. In addition, the sheet of phosphor Zn2SiO4:Mn2+,P benefits the luminous flux.